Synthesis of MnFeO3 from the oxidate thermal decomposition of Mn[Fe(CN)5NO]·2H2O - Lick, Ileana Daniela (2009)
On the basis of previous studies about the pentacyanonitrosylmetallates whose thermal decomposition generates different type of oxides, the Mn[Fe(CN)5NO]·2H2O was used as raw material to give FeMnO3. The decomposition was studied by Thermogravimetric (TGA-DTG) and Differential Thermal Analysis (DTA) under air atmosphere, between room temperature and 1200°C. IR spectroscopy and XRPD, refined by Rietveld analysis, were used to follow the process. The XRPD of the sample heated at different temperatures showed the following sequence: MnFe2O4 and (Mn,Fe)2O3 disordered bixbyte phases, until arriving to the final product, MnFeO3. Temperature programmed reduction (TPR) and EDS-EDAX analyses were used for the characterization, as well.